Selective cytotoxicity of organotin(IV) compounds with 2,3-dihydroxybenzyldithiocarbazate Schiff bases - Md Yusof, Enis Nadia; Mohamad Ishak, Nurul Nabihah; Mohammad Latif, Muhammad Alif; Mohamed Tahir, Mohamed Ibrahim; Sakoff, Jennette A.; Page, Alister J.; Tiekink, Edward R. T.; Ravoof, Thahira B. S. A. (Springer, 2020)
A series of tridentate ONS Schiff bases were synthesised via condensation by reacting 2,3-dihydroxybenzaldehyde with S-2-methylbenzyldithiocarbazate (S2MBDTC) (1), S-4-methylbenzyldithiocarbazate (S4MBDTC) (2) and S-benzyldithiocarbazate (SBDTC) (3) in an equimolar ratio (10 mmol). The Schiff bases were then reacted with diphenyltin(IV) and dimethyltin(IV) dichloride in an equimolar ratio (1 mmol) yielding six new organotin(IV) compounds (4–9). All the compounds were successfully characterised by elemental analysis, FT-IR, multinuclear NMR, UV–Vis, mass spectroscopy and molar conductivity. The molecular geometries for five compounds, 3, 5, 6, 8 and 9, have been established by X-ray crystallography. The five-coordinate geometry for each of the diorganotin molecules was defined by two carbon atoms from the tin-bound substituents as well as three donor atoms derived from the dinegative, tridentate dithiocarbazate ligands, namely thiolate-S, phenoxide-O and imine-N atoms. The resultant five-coordinate C2NOS geometries were intermediate between ideal square pyramidal and trigonal bipyramidal geometries. The diphenyltin(IV) compounds (4–6) exhibited particularly promising and selective cytotoxicity against the A2780 (ovarian), BE2-C (neuroblastoma), SJ-G2 (glioblastoma) and MIA (pancreas) cancer cell lines. The interactions of the compounds (4–9) with calf thymus (CT-DNA) were evaluated using an electronic absorption method, and 7, 8, 9 were found to have good DNA binding affinity. The molecular docking studies of compounds (4–9) with DNA revealed that the compounds interacted with duplex DNA via hydrogen bonding, hydrophobic and electrostatic interactions.